Hippocampal volume deficits associated with exposure to psychological trauma and posttraumatic stress disorder in adults: A meta-analysis - Woon, Fu Lye; Sood, Shabnam; Hedges, Dawson W. (Progress in neuro-psychopharmacology & biological psychiatry, 2010)
Trauma exposure itself in the absence of posttraumatic stress disorder (PTSD) may be associated with hippocampal volume deficits. We meta-analytically compared hippocampal volumes in PTSD subjects, in trauma-exposed subjects without PTSD, and in trauma-unexposed subjects. Using the words and phrases PTSD, neuroimaging, hippocampus, brain, violence, trauma, abuse, rape, war, combat, accident, and disaster, we searched major computerized databases to obtain candidate studies through 2008 for inclusion. We identified 39 hippocampal volumetric studies in adults with PTSD compared to control groups consisting of either trauma-exposed controls without PTSD or trauma-unexposed controls, or both. We meta-analytically compared left, right, and total hippocampal volumes between 1) PTSD subjects and a trauma-unexposed group, 2) PTSD subjects and a trauma-exposed group without PTSD, and 3) a trauma-unexposed group and a trauma-exposed group without PTSD. Hippocampal volumes were smaller in the PTSD group and trauma-exposed group without PTSD compared to the trauma-unexposed group. Further, the right hippocampus was smaller in the PTSD group compared to the trauma-exposed group without PTSD. Additionally, the right hippocampus was larger than the left in the PTSD and trauma-unexposed groups but not in the trauma-exposed group without PTSD. Hippocampal volume reduction is associated with trauma exposure independent of PTSD diagnosis, albeit additional hippocampal reduction was found in PTSD compared to the trauma-exposed group without PTSD.